Modificações do fixador externo para osteossíntese Umeral em pombos domésticos (Columba livia) - Dalmolin, Fabíola (2006)
The aim of this study was to evaluate two types of external fixators induced to correct humeral fracture in eighteen domestic pigeons. The reduction of an diaphyseal humeral fracture was made with an intramedulary pin associated to another perpendicular one inserted into the distal segment (Group A - GA); in the other group (Group B - GB), an additional pin was used in the proximal fragment. All the pigeons were evaluated clinically and radiographically up to 60 days post surgery, except four of each group which were submitted to euthanasia at 15, 22 29 and 36 days for the macro and microscope exams. The flight test was successful in all pigeons. The bone calus was radiografically visible only in the GA; the mean time and the standard deviation for flight was 32,25 ± 6,5 days for the GA and 39,8 ± 3,83 for the GB. The mean time and standard deviation for fracture healing was 36 ± 0 days in the GA and 34 ± 3,4 in the GB. The anatomy pathological studies revealed that the bone consolidation process in the GB ocurred earlier than in the GA. The two types of external fixator evaluated were efficient to stabilized the fracture site allowing complete consolidation and return to function. The use of the external fixator with two perpendicular pins provide more stability at the fracture site although it s necessary more time for the surgery.